Artificial Intelligence in Manipulation: The Significance and Strategies for Prevention - Kavoliūnaitė-Ragauskienė Eglė (Baltic Journal of Law & Politics)
Manipulation has always been a persistent aspect of society, but the rise of artificial intelligence has significantly amplified its scope and impact. AI’s ability to access and process vast amounts of personal data has revolutionized the way individuals can be targeted with specific information. This technology enables the rapid delivery of highly personalized messages, making it easier to exploit psychological vulnerabilities and influence decision-making without the individual’s awareness.